2014
DOI: 10.1038/npp.2014.66
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Cocaine Self-Administration Influences Drug Seeking in the Rat: Optogenetic Evidence for a Role of the Prelimbic Cortex

Abstract: High-frequency intake and high drug-induced seeking are associated with cocaine addiction in both human and animals. However, their relationships and neurobiological underpinnings remain hypothetical. The medial prefrontal cortex (mPFC), basolateral amygdala (BLA), and nucleus accumbens (NAc) have been shown to have a role in cocaine seeking. However, their involvement in regulating highfrequency intake and high cocaine-induced seeking is unclear. We manipulated frequency of cocaine self-administration and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 40 publications
3
50
0
Order By: Relevance
“…Inhibiting projections from the anterior cingulate to the NAcore increases motivation to obtain cocaine under a PR schedule of reinforcement, delays subsequent extinction, and increases reinstatement (Kerstetter et al, 2016). This is in line with other work suggesting a differential role of the PLC-to-NAcore circuitry during different stages of the addiction process (Chen et al, 2013;Martín-García et al, 2014).…”
Section: A Nucleus Accumbens Coresupporting
confidence: 89%
“…Inhibiting projections from the anterior cingulate to the NAcore increases motivation to obtain cocaine under a PR schedule of reinforcement, delays subsequent extinction, and increases reinstatement (Kerstetter et al, 2016). This is in line with other work suggesting a differential role of the PLC-to-NAcore circuitry during different stages of the addiction process (Chen et al, 2013;Martín-García et al, 2014).…”
Section: A Nucleus Accumbens Coresupporting
confidence: 89%
“…Importantly, the rats that developed a burst-like pattern of cocaine use did not differ from the other rats with respect to cumulative cocaine intake. Similarly, by dividing rats into two groups based on their spontaneous, selfimposed interval between cocaine infusions, Martin-Garcia et al (2014) found that rats showing high-frequency cocaine selfadministration are more vulnerable to cocaine-primed reinstatement of drug-seeking behaviour relative to rats with low-frequency cocaine intake-in spite of equivalent levels of prior drug intake. Together, these findings suggest that an intermittent pattern of use, more than the amount of drug used, governs the susceptibility to increased drug use.…”
Section: A New Model: Intermittent Access To Drug During a Longaccessmentioning
confidence: 99%
“…The intake of cocaine at short (2 min) rather than longer (6 min) intervals within each self-administration session preferentially increases c-Fos protein levels in the prelimbic and infralimbic cortices, the nucleus accumbens shell and core and the basolateral nucleus of the amygdala (Martin-Garcia et al, 2014). Optogenetic manipulations also show that neuronal activity within the prelimbic cortex regulates cocaine-seeking and -taking behaviours only in animals allowed to selfadminister cocaine at short inter-infusion intervals (MartinGarcia et al, 2014).…”
Section: Pharmacokinetics Determine the Neuroplasticity Evoked By Drugsmentioning
confidence: 99%
“…After a period of cocaine abstinence, which has the impact of incubating, or upregulating craving for cocaine (Grimm et al, 2001), c-fos , zif268 , and ARC mRNA are all elevated in PL (Hearing et al, 2008). A recent study investigating low- vs. high-frequency cocaine use models demonstrated that high-frequency cocaine self-administration increased Fos in PL, and that optogenetic inhibition of PL decreased cocaine prime-induced reinstatement in this population of animals (Martin-Garcia et al, 2014). Cocaine self-administration also increases spines and dendritic bulbs in PL (Robinson et al, 2001).…”
Section: Dichotomous Functions For Dorsal (Pl) and Ventral (Il) Mpfc mentioning
confidence: 99%